2023
DOI: 10.1111/tpj.16155
|View full text |Cite
|
Sign up to set email alerts
|

Puncta‐localized TRAF domain protein TC1b contributes to the autoimmunity of snc1

Abstract: Immune receptors play important roles in the perception of pathogens and initiation of immune responses in both plants and animals. Intracellular nucleotide-binding domain leucine-rich repeat (NLR)-type receptors constitute a major class of receptors in vascular plants. In the Arabidopsis thaliana mutant suppressor of npr1-1, constitutive 1 (snc1), a gain-of-function mutation in the NLR gene SNC1 leads to SNC1 overaccumulation and constitutive activation of defense responses. From a CRISPR/Cas9-based reverse g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 151 publications
0
2
0
Order By: Relevance
“…Immune receptors play important roles in the perception of pathogens and the initiation of immune responses in both plants and animals. A study by Ao et al 76 identified mutations in TRAF CANDIDATE 1b ( TC1b ), a gene encoding a protein with four tumor necrosis factor receptor-associated factor (TRAF) domains that were shown to suppress snc1 phenotypes underlying immune receptors. TC1b also does not physically associate with SNC1, affect SNC1 accumulation, or affect signaling of the downstream helper NLRs represented by ACTIVATED DISEASE RESISTANCE PROTEIN 1-L2 (ADR1-L2), suggesting that TC1b uniquely impacts snc1 autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Immune receptors play important roles in the perception of pathogens and the initiation of immune responses in both plants and animals. A study by Ao et al 76 identified mutations in TRAF CANDIDATE 1b ( TC1b ), a gene encoding a protein with four tumor necrosis factor receptor-associated factor (TRAF) domains that were shown to suppress snc1 phenotypes underlying immune receptors. TC1b also does not physically associate with SNC1, affect SNC1 accumulation, or affect signaling of the downstream helper NLRs represented by ACTIVATED DISEASE RESISTANCE PROTEIN 1-L2 (ADR1-L2), suggesting that TC1b uniquely impacts snc1 autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Both calcium-binding protein MtPBP1 and peroxidase MtPrx28 are involved in ROS signaling and defense responses [35][36][37][38]. MATH domain-containing proteins have been shown to regulate NLR turnover in A. thaliana [39,40]. The top ten most upregulated DEGs in the resistant genotype occurred at 72 hpi, while the top ten downregulated DEGs occurred at all time points.…”
Section: Unique Degs In the Resistant Genotype Highlight Potential Ge...mentioning
confidence: 99%